Remediação de águas subterrâneas contaminadas com cromo (VI) por meio de uso de turfa e lama vermelha - Santos, Marilia Mayumi Augusto dos [UNIFESP] (2015)
The contamination of aquifers by hexavalent chromium has been increasing in recent years, due to the intense industrial activity. The remediation of groundwater is based on conventional processes where Cr(VI) (highly toxic and mobile) is reduced to Cr(III) (more stable and less toxic in trace concentrations) which is precipitated as hydroxides. This study was motivated by an actual case of CR(VI) aquifer contamination within the watershed protection area of Billings, located in Diadema (SP). The objective is to experimentally evaluate the use of two alternative materials such as red mud (alumina?s residue production from bauxite) and peat, the in-situ treatment (in permeable reactive barriers) of CR(VI) contaminated groundwater. The main characteristics and properties of these materials were investigated to verify the removal capacity of Cr(VI). Batch tests were conducted using solutions of Cr(VI) prepared with deionized water and underground water. The efficiency of the red mud in the CR(VI) removal was affected by the alkalinity of the material which did not favor neither adsorption nor the reduction of Cr(VI) solution. The studied peat performed better behavior, by a high organic matter content (35.4%), responsible for the CR(VI) reduction and the CR(III) complexation. In conditions observed in underground water (pH approximately 6), it was found that the predominant cation exchange process and that the mechanism of reduction of Cr(VI) is very slow, but increases with time. In general, each gram of peat removed approximately 0.4 mg and 1 mg of Cr(VI) in 1 day of contact with solutions prepared respectively with distilled water and underground water. This removal increased to about 2 mg g-1 in 5 days in both solutions. It was observed that this efficiency is also affected by the pH environmental conditions: pH of groundwater (around 6), the removal efficiency of Cr(VI) by peat was 30%, whereas at pH 2, around 95%. This happens due to Cr(VI) be easily reduced to Cr(III) in acid media. It also tested the Cr(VI) removal efficiency by peat in fixed bed columns reactive barriers to simulate this test it was observed that each gram of peat removes 1.7 mg Cr(VI). It is still a half-life of about 4.4 hours. The results of this study suggest that organic matter of peat promotes the reduction of Cr(VI) to Cr(III), which is then adsorbed by the components of peat and also complexed to organic substances of such material.